Pengaruh Peran Human Resources Development (HRD) Dalam Meningkatkan Produktivitas Kerja Karyawan Pada PT. Bakrie Sumatera Plantations Tbk - Muhammad Andre Wardhana; Zainarti Zainarti (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
Improving the quality of human resource performance depends on factors that are influenced by the job satisfaction they receive and feel from an organization. The satisfaction and dissatisfaction felt by employees in carrying out their duties is something that always exists in an organization. The purpose and benefits of the research as a result of the internship carried out by the author is that the company can be better in the future and maximize aspects of company employee satisfaction in order to create work comfort and performance productivity and their employees will be better and maximized for the PT. Bakrie Sumatera Plantations Tbk.